Asymptomatic prostatic abscess: a cause of staphylococcal bacteraemia in uncontrolled diabetes. (14th October 2013) - Hunt, L; Vinayagam, R; Gopalan, P; Bains, A; Scott, AR
Abstract Prostatic abscess is a rare and difficult condition to diagnose. Here we report two cases of type 2 diabetic patients with similar presenting features. Both had uncontrolled diabetes mellitus on admission and grew Staphylococcus aureus from blood cultures and aspirates. Diagnosis was made following computed tomography and magnetic resonance imaging. Treatment was with intravenous antibiotics and no surgical intervention was required. Copyright © 2013 John Wiley & Sons.